Insights into Early Systemic Treatment in Atopic Dermatitis: Scientific Facts and Practical Considerations - Efstratios Vakirlis; Stamatios Gregoriou; Katerina Bakirtzi; Eleni Paschou; Aikaterini Tsiogka; Ilias Papadimitriou; Eleni Sotiriou (Adis, Springer Healthcare, 2024)
Abstract Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized clinically by pruritus, and pathophysiologically by immune dysregulation, and compromised skin barrier function. While topical therapies are currently the cornerstone of AD management, especially in mild disease, recent advancements in systemic treatments and a deeper understanding of similar skin diseases, such as psoriasis, have highlighted the importance of early intervention. In this commentary, we explore the potential benefits of early systemic intervention in AD, with pruritus determining such a decision. Building on this concept, we assume that, through the timely systemic treatment that targets the immune dysregulation present in AD, the progression of the disease could be modified, improving overall patient outcomes. Early systemic intervention may minimize systemic inflammation, halting the "atopic march" and disrupting the "itch-scratch" cycle. Managing pruritus at its root could prevent secondary complications and reduce the psychosocial burden of the disease. This paradigm shift fosters a collaborative healthcare approach that empowers patients with long-term disease control strategies. In conclusion, the safety and efficacy of novel systemic treatments offer a compelling scenario for early intervention in atopic dermatitis care.